SIMULASI TEKNIK MODULASI OFDM QPSK DENGAN MENGGUNAKAN MATLAB - Rosalia H. Subrata; Ferrianto Gozali (Jetri : Jurnal Ilmiah Teknik Elektro, 2015)
This paper provides a brief explanation of the processing steps involved in Orthogonal Frequency Division Multiplexing (OFDM) with Quadrature Phase Shift Keying (QPSK) modulation technique implemented as a simulation program in MatLab. Input data of the simulation program in the form of random bit stream or text can be selected by users. The process conducted in the simulation is divided into three consecutive steps, processes in the OFDM transmitter, in transmission channel and in the OFDM receiver. The result of computation and the wave form involved in every processing steps will be displayed during the simulation. The final result shows, how the input data go through processing steps in the OFDM transmitter, transmission channel with noise and finally received by OFDM receiver will produce the output, random bit stream or text, exactly similar with input data